DOCUMENTING LANGUAGES USING NATURAL SEMANTIC METALANGUAGE THEORY: A CASE STUDY OF ‘SEE’ AND ‘FALL’ IN KUPANG MALAY LANGUAGE - David Samuel Latupeirissa (International Journal of Linguistics and Discourse Analytics, 2020)
There are some approaches that can be applied to documenting local languages. One of them is an approach of Natural Semantic Metalanguage (NSM) theory. This paper aims to present a case study of a local language documentation – in this case, lexicosemantic documentation - using NSM as a brief example of documenting local language. The lexicons presented in this paper are verbs ‘see’ and ‘fall’ in Kupang Malay Language (KML). KML itself is a local language in East Nusa Tenggara Province- Indonesia (Latupeirissa, 2016a). Scientifically, this language is a creole language (Jacob and Grimes, 2003) that formed by local languages migration and diaspora (Latupeirissa, 2016b, 2017). Research data has been collected by combining two methods, namely: Documentation Method and Linguistic Field Research Method. For Documentation Method, researchers gained data from (1) KML Bible, (2) KML dictionary, and (3) Tapaleuk Column in Pos Kupang Newspaper. For Linguistic Field Research Method, researchers gained data through daily conversation and interview. Next, the researchers use paraphrase/ explication technique to discuss the result. The result shows that lexicon ‘See’ has five different semantic meaning in KML. They are ‘lia’, ‘loti’, ‘malerok’, ‘maloi’ and ‘pe’e mata’, while lexicon ‘Fall’ has seven different semantic meaning in KML, namely ‘jato’, ‘rubu’, ‘malenggang’, ‘tikam mulu’, ‘tikam kapala’, ‘taroso’, ‘puku panta’.